Spontaneous Intake and Long-Term Effects of Essential Oils After a Negative Postnatal Experience in Chicks - Guilloteau, Laurence A.; Collin, Anne; Koch, Alexia; Leterrier, Christine (Frontiers in Veterinary Science, 2019)
The postnatal period is critical for broiler chicks as they are exposed to potentially stressful environmental changes in the hatchery and during transportation to the rearing houses. The ability of broiler chicks to spontaneously drink essential oils (EO) to mitigate the effects of a negative postnatal experience was tested. Chicks were placed in the rearing facility either immediately (C group), or after a 24h-delay period (D group) to mimic a delay in transportation possible under commercial conditions. In experiment 1, each group had access to either water only or to water and one EO (cardamom, marjoram or verbena) from D1 to D13. Verbena EO intake was higher in the D group than in the C group from D1 to D6 and cardamom EO intake was lower in the D group than in the C group from D6 to D13. In experiment 2, half of the groups had access to water only and the other half had both water and the three EO simultaneously. Chicks from D and C groups chose the EO similarly except for cardamom EO with a lower intake being observed in the D than in the C group from D6 to D12. The delayed placement of the D group reduced chicken growth until 34 days of age and temporarily increased the feed conversion ratio, but did not affect their welfare or the prevalence of health disorders. The EO intake did not mitigate the growth reduction in D group chicks, but did mitigate the reduced Pectoralis major muscle yield. In conclusion, chicks were able to make spontaneous choices regarding EO intake according to their postnatal experience when EO were presented individually, but not when presented simultaneously as in our experimental design. The EO intake only partially mitigated the decrease in chicken performance after the negative postnatal experience.